Specific effect of interferon on the herpes simplex virus type 1 transactivation event. - De Stasio, P R (1990)
Human recombinant gamma interferon and to a lesser extent alpha interferon were shown to inhibit herpes simplex virus type 1 replication in the human cell lines WISH and HEp-2. Dot blot analysis of viral DNA synthesis and viral RNA transcription indicated that the inhibition occurred at an early step in infection. A study of the early events after herpes simplex virus type 1 infection indicated that adsorption, penetration, uncoating, and transport of viral DNA were not affected by interferon. Northern (RNA) blot analysis revealed that both immediate-early and delayed-early gene transcription was inhibited by interferon. Transactivation of the immediate-early responsive element linked to a reporter gene (CAT or tk) was specifically inhibited by both classes of interferon. Our data would indicate that either the transactivating protein VP16 or the complex formed between VP16 and a host protein(s) is attenuated by interferon.